Development of Motorized Walnut Dehuller - Ali, Mudasir; Dixit, Jagvir; Lohan, Shiv Kumar (Journal of Agricultural Engineering, 2018)
Most of walnut production is manually hulled in India. Green walnut is processed in dry condition by removing the outer shell. Removing of outer shell of walnut with a knife by hand is difficult at a low production rate of 0.025- 0.030 t.h-1. A motorized walnut dehuller based on the principle of shearing-off the hull of a green walnut by shearing force was developed and evaluated, with peripheral speed and number of heaping days being optimized to make the best quality of hulling process. Results indicated that the effective throughput capacity, hulling efficiency and fully hulled walnut percentage increased with increase in peripheral speed. Similarly, hulling efficiency increased with increase in number of heaping days before hulling, but the fruit shell staining and kernel discoloration took place with increase in the number of heaping days after harvest. At peripheral speed of 6.41 m.s-1 and 4-day heaping period, the hulling capacity of the developed machine was 0.260 t.h-1 with hulling efficiency of 79.55 per cent.